2000 Annual Review of Development Effectiveness : From Strategy to Results (Independent Evaluation Group Studies, 2001)
This Annual Review of Development Effectiveness (ARDE) builds on previous reviews, i.e., the 1998 review, released in a hostile environment of financial crisis, concluded that improvements in project performance cannot be enough, that improvements at a higher plane of program, and country performance should also be present; and, the 1999 review, inscribed within the Comprehensive Development Framework dilemmas, and challenges, identified practices for dealing with those challenges, namely to be based on country commitments to poverty reduction, and sustainable growth. The ARDE 2000 finds that progress was solid on a broad front, but that further progress is likely. Portfolio performance is likely to exceed the Strategic Compact target of seventy five percent satisfactory outcomes; and, sustainability, and institutional development ratings reflect improvements. Though progress is commendable, this review examines four tensions the Bank faces: learning to reconcile client, and corporate priorities; adapting global prescriptions to local conditions; balancing country performance and poverty incidence in allocating its resources; and, achieving efficiency/selectivity, seeking to implement a holistic vision of development. Bank strategies should acknowledge client needs, judicious adaptation to institutional, social, and political fronts should be pursued, and, an approach to poor-performing countries should be addressed